KUALITAS PELAYANAN PADA PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK (P2TP2A) KARTIKA KABUPATEN KEBUMEN - Unggul Winarti; Paulus Israwan Setyoko; Swastha Dharma (Program Magister Administrasi Publik, Fakultas Ilmu Sosial dan Politik, Universitas Jenderal Soedirman, 2016)
The research aims to examine quality of service conducted by P2TP2A Kartika for violence victims in Kebumen. To find out the problem happened, this research using theory of service quality Consisting five dimension there are reliability, responsiveness, assurance, empathy, and tangible. This research use qualitative approach. With this type of research was carried out to give an idea of ​​the quality of service at the Integrated Service Center for Empowerment of Women and Children (P2TP2A) Kartika Kebumen in detail. Parties became key informants are the victims of violence, while to ensure the validity of the data, which is an additional informant among others: Kartika P2TP2A officer ranks, and institutions that are associated with P2TP2A Kartika. Data collected through interviews, documentation and observation. The data analysis is using interactive model analysis. The results showed that P2TP2A Kartika as community-based organizations generally, women's empowerment and child protection, in compliance with the five aspects of services that consisting, reliability, responsivenesss, assurance, empathy and tangible in accordance with the commitment to achieve the goal to prevent and eliminate violence against women and children, preventive, curative, and rehabilitative. Constraints faced in the provision of services to the Office P2TP2A Kartika, among others, the staffing policies that lack sufficient capacity to provide services to the community. While the obstacles in the completion of the case is the lack of public understanding of the law that led to the loss of evidence and expert agents who are already facing so difficult to ensnare the perpetrators of violence. The efforts to develop the quality of service and capacity were through technical training and capacity building P2TP2A Kartika. Intended gather to program which direct to autonomous of P2TP2A finally able to play role more optimal in society e.g P2TP2A should have operating standard procedure appropriate with minimum standard of service those set in. Keywords: Domestic Violence, Integrated Service Center for Empowerment of Women and Children (P2TP2A), Quality of Service